Preparation and Characterization of Mg–Al–B Alloy (Mg0.5Al0.5B2) Via High-Temperature Sintering - Lin Yang (Materials, 2021)
Boron and its alloys have long been explored as potential fuel and increasingly replace pure aluminum powder in high-energy formulations. The ignition and burning properties of boron can be improved by making boron alloys. In this study, an Mg–Al–B alloy was synthesized from magnesium, aluminum and boron powders in a 1:1:4 molar ratio by preheating to 600 °C for 30 min, followed by high-temperature sintering in a tube furnace. The effects of sintering temperature (700–1000 °C) and holding time (0.5–10 h) on the phase composition of mixed powders were studied. After the samples were cooled to room temperature, they were ground into powder. The phase composition, micromorphology and the bonding forms of elements of the synthesized samples were studied using XRD, SEM and XPS. The results show that each element exists in the form of simple substance in the alloy. The influence of the sintering temperature on the synthesis reaction of Mg0.5Al0.5B2 is very important, but holding time has little effect on it. With the increase of sintering temperature, the content of the Mg0.5Al0.5B2 phase gradually increases, and the phase content of residual metal gradually decreases. The phase and morphology analyses show that the optimum sintering temperature is 1000 °C with a minimum holding time of 0.5 h. It is expected to be used in gunpowder, propellant, explosives and pyrotechnics with improved characteristics.